The Gaza Monologues Part II: Iman Aoun in conversation with Marina Johnson - Johnson, Marina (Education & Theatre, 2025)
This interview is the second part of our focus on The Gaza Monologues and ASHTAR Theatre in the current issue (see also The Gaza Monologues: Part I, pp. 92–97). Specifically, Marina Johnson talks to Iman Aoun, the co-founder and executive director of ASHTAR Theatre, a leading Palestinian theatre company based in Ramallah which is recognised for its commitment to social justice through performance. One of its bestknown projects is The Gaza Monologues, a powerful series of testimonies written by young people in Gaza in the aftermath of the 2008–2009 Israeli offensive. The interview further elaborates the discussion of ASHTAR Theatre’s work and Aoun’s artistic and political vision.